SOG’LOM OVQATLANISH FIZIOLOGIYANING DOLRAZB MUAMMOLARI YECHIMLARI - Gurman, Efroim; Zaripov, Bahriddin; Ummatqulov, Sh; Axmedova, Gulsara (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
SOG’LOM OVQATLANISH FIZIOLOGIYANING DOLRAZB MUAMMOLARI YECHIMLARI